Assessment of toxicity and oxidative stress associated with omeprazole in Caenorhabditis elegans - Gabriela Endres da Rocha Pompeo; Roberta Rodrigues Zorzo; Bianca Bordignon Fraga; Mariele Feiffer Charão; Magda Susana Perassolo (Acta Scientiarum. Biological Sciences, 2025)
Omeprazole is an inhibitor of the proton pump which has been extensively studied presently due to the evidence of a potential toxicity related to the generation of reactive species of oxygen (ROS) to its chronic users. Thus, this study aimed to assess the toxicity and oxidative stress of omeprazole in Caenorhabditis elegans. Survival assays, nematode body length and ROS generation trials were carried out after the exposure of C. elegans to omeprazole. The omeprazole used for the treatment of nematodes was the commercial standard in pellets. The pellets were dissolved in a bicarbonate solution (84 mg mL-1) to a 10 mg mL-1 concentration. The N2 wild strain of C. elegans was kept in NGM medium, incubated at 20°C and supplemented with E. coli OP50 as food source. Nematodes in L1 stage were obtained through synchronization and, afterwards, 1500 nematodes were exposed to 5 concentrations of omeprazole (62.5 μg mL-1, 125 μg mL-1, 250 μg mL-1, 500 μg mL-1, 1 mg mL-1). The generation of ROS was assessed through fluorescence in a 0.05 mM 2’,7’-dichlorofluorescein diacetate (DCF-DA) solution. The exposure of C. elegans to omeprazole reduced size (p < 0.05), survival (p < 0.05) and increased generation of ROS (p < 0.05) in a dose-dependent manner. The lethal dose (DL50) was determined as 968 μg mL-1. Bicarbonate, omeprazole diluent, was tested as control and did not present any significant alteration (p > 0.05). The decrease in survival and body length of nematodes treated with omeprazole and the generation of ROS confirm its toxicity.